Simulation-based decision support for production improvement using integrated ergonomic and productivity performance indicators. (22nd June 2021) - Barkokebas, Regina Dias; Ritter, Chelsea; Al-Hussein, Mohamed; Li, Xinming
Workers in the construction manufacturing industry are exposed to labour-intensive tasks with ergonomic risks such as forceful exertion and repetitive motion. Due to increased productivity and repetitive motions resulting from improvement initiatives implemented in offsite construction manufacturing, the investigation of ergonomic risks associated with these changes is needed. In this context, this paper explores an existing panelised floor production line aiming to minimise its ergonomic risks while improving its current productivity rate. Information pertaining to human body motion and productivity is extracted from video recordings. The ergonomic risks associated with specific tasks are identified using two existing ergonomic risk assessment methods: the rapid entire body assessment and the rapid upper limb assessment. A simulation model is used to evaluate various process improvements from the perspective of both ergonomic risks and productivity to support the decision-making process and the prioritisation of process changes in the factory.